The smallest minority : independent thinking in the age of mob politics - Williamson, Kevin D (Regnery Gateway, an imprint of Regnery Publishing, 2019)
"Reader beware: Kevin D. Williamson the lively, literary firebrand from National Review who was too hot for The Atlantic to handle, comes to bury democracy, not to praise it. With electrifying honesty and spirit, Williamson takes a flamethrower to mob politics, the “beast with many heads” that haunts social media and what currently passes for real life. Its destroying our capacity for individualism and dragging us down “the Road to Smurfdom, the place where the deracinated demos of the Twitter age finds itself feeling small and blue.” The Smallest Minority is by no means a memoir, though Williamson does reflect on that “tawdry little episode” with The Atlantic in which he became all-too-intimately acquainted with mob outrage and the forces of tribalism. Rather, this book is a dizzying tour through a world you'll be horrified to recognize as your own. With biting appraisals of social media (“an economy of Willy Lomans,” political hustlers (“that certain kind of man or woman who will kiss the collective ass of the mob”), journalists (“a contemptible union of neediness and arrogance”) and identity politics (“identity is more accessible than policy, which requires effort”), The Smallest Minority is a defiant, funny, and terrifyingly insightful book about what we human beings have done to ourselves." -- provided by publisher